Genetic control of the sensory quality of coffee beverage - Alixandre, Fabiano Tristão; Ferreira, Marcia Flores da Silva; Ferreira, Adesio; Alixandre, Ricardo Dias; Dias, Rodrigo da Silva; Lima, Paula Aparecida Muniz de; Holtz, Filipe Garcia; Macette, Higor Alixandre (Seven Editora, 2023)
The sensory quality of coffee drink is a quantitative characteristic, that is, polygenic, being directly associated with compounds such as: caffeine, trigonellin, lipids, proteins, sucrose and chlorogenic acids that are precursors of aromas and flavors in coffee. Thus, the objective of this review was to identify the main genes related to the synthesis of these compounds and to understand how the expression of these genes occurs throughout the development of coffee fruits. The studies studied in the review demonstrate that the use of molecular biology has allowed greater advances not only in the identification of the main compounds related to the sensory quality of coffee drink, but also in the identification of enzymes involved in its biosynthesis and the main genes that control the synthesis of these enzymes. The deepening of these studies generates great expectations, because it may enable the development of strategies that can control the expression of these genes and thus interfere in the chemical constitution of the grains in a favorable way for the production of quality precursor compounds. Another important aspect raised in the review was the study of genes associated with fruit development and maturation, and it is possible to verify how the expression of these genes occurs throughout the period of fruit development and how they are responding to environmental stimuli and controlling fruit maturation. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-112